2016
DOI: 10.3238/arztebl.2016.0645
|View full text |Cite
|
Sign up to set email alerts
|

Yoga in Women With Abdominal Obesity

Abstract: The 12-week yoga intervention had moderately strong positive effects on anthropometric and self-reported variables in women with abdominal obesity. Yoga is safe in this population and can be recommended as a technique for combating abdominal obesity in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 37 publications
1
46
0
3
Order By: Relevance
“…According to one RCT, yoga intervention had moderately strong positive effects on anthropometric variables in women with abdominal obesity. Yoga is safe in women and can be recommended as a technique for combating abdominal obesity in women [21]. Our study provides efficacy of Yoga in same concern in adolescent population.…”
Section: Discussionmentioning
confidence: 55%
“…According to one RCT, yoga intervention had moderately strong positive effects on anthropometric variables in women with abdominal obesity. Yoga is safe in women and can be recommended as a technique for combating abdominal obesity in women [21]. Our study provides efficacy of Yoga in same concern in adolescent population.…”
Section: Discussionmentioning
confidence: 55%
“…In a fifteen-day comparative controlled trial, yoga reduced the body mass index and waist circumference, while the ability to balance and the handgrip strength increased [29]. A randomized controlled trial assessing the effects of yoga on female adults with abdominal obesity reported a reduction in perceived stress levels along with other favourable changes in mental health-related outcomes such as the health-related quality of life, self-esteem, better body awareness, and trust in bodily sensations following twelve weeks of yoga [30]. The results of these studies indicate that yoga decreases physical and psychological efforts required to be physically active in persons with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The trial profile is provided in Figure 1 . The sample size was determined from a previous study on centrally obese females ( 8 ). A required sample size ( n = 20) was obtained using Cohen's formula for the effect size of 0.40 calculated from the mean and SD values of waist circumference which were changed significantly after 12 weeks of yoga, alpha at 0.05, powered at 0.90 using G power software ( 10 ).…”
Section: Methodsmentioning
confidence: 99%
“…A single study demonstrated a decrease in central obesity in 60 female participants after 12 weeks of yoga ( 8 ). This inference was based on the waist circumference.…”
Section: Introductionmentioning
confidence: 99%